The Role of Indonesian Indigenous Cyanobacteria Culture Collection as An Ex-situ Conservation Effort and Microalgae Biodiversity Study Material - Nining Betawati Prihantini (Postgraduate, University of Mataram, 2023)
Exploratory research has been carried out on Indonesian indigenous Cyanobacteria in an effort to collect these isolates to be used as learning materials for microalgae biodiversity. Cyanobacteria are known as photosynthetic bacteria and prokaryotic microalgae. The members of the cyanobacteria found were isolated, cultured, identified, and collected. The location for sampling cyanobacteria is the UI Depok campus area which consists of water from small lakes (situ) and soil. The results showed that 22 strains of Cyanobacteria were isolated and cultured properly, and consisted of 12 genera/species, namely Merismopedia sp. (1 isolate), Synechococcus sp. (1 isolate), Limnothrix redekei (1 isolate), Oscillatoria sp.1 (1 isolate), Oscillatoria sp.2 (1 isolate), Pseudanabaena sp. (3 isolates), Nostoc sp. (4 isolates), Anabaena sp. (1 isolate), Scytonema sp. (1 isolate), Fischerella sp. (1 isolate), Stigonema sp. (1 isolate), and Hapalosiphon sp. (6 isolates). Twenty-two (22) strains were then collected and treated by subculture method. Of the 11 genera found, there are 3 genera that have been known as genera that have potential as sources of biobased materials, biofuels, biofertilizers, and others, namely Synechococcus, Nostoc, and Anabaena